2019
DOI: 10.1088/1361-6528/ab0ce0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and coloration of highly dispersive SiO2/BiVO4 hybrid pigments with low cost and high NIR reflectance

Abstract: Highly dispersed SiO2/BiVO4 hybrid pigments with a spherical structure and high near-infrared (NIR) reflectance have been successfully fabricated by a facile sol–gel method followed by calcination. The dispersed and uniformly spherical particles of the hybrid pigments were caused by the support provided by SiO2 microspheres, and their color was adjusted via the band-gap energy, which was changed with the incorporation of SiO2 microspheres. The SiO2/BiVO4-3 hybrid pigment presented higher yellow hues (b* = 91.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…These obtained results indicate that the introduction of SiO 2 (37.5% in mass content) does not affect the chromatic properties of BiVO 4 pigment. A similar phenomenon was also found for the synthesis of hybrid SiO 2 /BiVO 4 pigments, with SiO 2 as the core, by He et al [33]. The addition of SiO 2 is expected to decrease the use cost of yellow pigment greatly since BiVO 4 is much more costly than SiO 2 .…”
Section: Chromatic and Spectroscopic Properties Of Bivo 4 @Sio 2 Pigm...supporting
confidence: 75%
“…These obtained results indicate that the introduction of SiO 2 (37.5% in mass content) does not affect the chromatic properties of BiVO 4 pigment. A similar phenomenon was also found for the synthesis of hybrid SiO 2 /BiVO 4 pigments, with SiO 2 as the core, by He et al [33]. The addition of SiO 2 is expected to decrease the use cost of yellow pigment greatly since BiVO 4 is much more costly than SiO 2 .…”
Section: Chromatic and Spectroscopic Properties Of Bivo 4 @Sio 2 Pigm...supporting
confidence: 75%
“…Infrared sintering technology is a photonic sintering approach for metal nanoparticles [38][39][40]. In this work, the infrared sintering process is used to promote the deformation of PVP on the surface of AgNPs and improve the conductivity of the silver film.…”
Section: Infrared Sintering and Conductivity Of Silver Electrodesmentioning
confidence: 99%
“…In recent years, it has been recognized as an effective way for blocking solar radiation energy to reduce indoor temperature by developing the smarter nontoxic near-infrared reflective (NIR) cool inorganic pigments [2][3][4]. It was confirmed that the temperature difference could reach 10 °C before and after coating NIR inorganic pigments with high solar reflection and thermal emissivity [5,6]. It is well-known that the spectrum of the solar rays also includes ultraviolet (UV) (5%) and visible light (43%) in addition to near-infrared waveband (52%) [7].…”
Section: Introductionmentioning
confidence: 99%
“…At present, some colored non-toxic NIR and infrared radiative pigments had presented great broad application prospects in the field of energy-saving architectural coatings [5,6]. As an environment-friendly yellow inorganic pigments, bismuth yellow (BiVO 4 ) has been identified as an ideal substitute for conventional industrial inorganic yellow pigments (e.g.…”
Section: Introductionmentioning
confidence: 99%